How isotopic signatures relate to meat consumption in wild chimpanzees: A critical reference study from Taï National Park, Côte d'Ivoire. Issue 146 (September 2020) - Oelze, Vicky M.; Wittig, Roman M.; Lemoine, Sylvain; Kühl, Hjalmar S.; Boesch, Christophe
Abstract: The roots of human hunting and meat eating lie deep in our evolutionary past shared with chimpanzees ( Pan troglodytes ). From the few habituated wild populations, we know that there is considerable variation in the extent to which chimpanzees consume meat. Expanding our knowledge of meat eating frequencies to more, yet unhabituated, populations requires noninvasive, indirect quantitative techniques. We here evaluate the use of stable isotopes to reconstruct meat-eating behavior in wild chimpanzees. We present hair isotope data ( n = 260) of two western chimpanzee ( P. troglodytes verus ) groups from Taï forest (Côte d'Ivoire) and relate them to directly observed amounts of meat consumed, sex/female reproductive state, and group, while controlling for differences between individuals, seasons, and observation efforts. Succeeding seven months of hunting observations, we collected hair of 25 individuals for sequential analysis of δ 15 N and δ 13 C. Hunting success in the 7-month study period varied between the groups, with 25 successful hunts in the East group and only 8 in the North group. However, our models only found a direct relationship between amounts of meat consumed and variation within individual hair δ 15 N values in the East group, but not in the North group and not when comparing between individuals or groups. Although on average East group individuals consumed more than double the amount of meat than North group individuals, their δ 15 N values were significantly lower, suggesting that differences in microhabitat are substantial between group territories. The effect of sex/female reproductive state was significant in δ 15 N and δ 13 C, suggesting it related to access to food or feeding preferences. We conclude that several factors additional to diet are influencing and thus obscuring the isotope ratios in wild chimpanzee hair, particularly when comparing between sexes and social groups.